Karakteristik fungsional hidrolisat kolagen kulit tuna yang dihidrolisis dengan pepsin dari lambung tuna: Functional characteristics of tuna skin collagen hydrolyzed by tuna gastric pepsin - Muttaqin, Roisul Adi Brilianto; Tati Nurhayati; Abdullah, Asadatun (Jurnal Pengolahan Hasil Perikanan Indonesia, 2026)
Collagen hydrolysis can be performed using solvent extraction, chemical degradation, fermentation, and enzymatic methods, among others. Hydrolysates produced using enzymes contain bioactive peptides that are beneficial for health. Specific motifs produced during hydrolysis, such as prolinae/hydroxyprolinae and glycine sequences, or prolinae at the C-terminus, are often associated with ACE-inhibitory bioactivity or antioxidant effects. Hydrolysates can be produced using byproducts of the fisheries industry, such as yellowfin tuna skin as a source of collagen and tuna stomach as a source of collagen-hydrolyzing pepsin. This study aimed to identify the optimal pepsin activity and hydrolysis temperature for producing collagen hydrolysate using pepsin derived from tuna stomach. The research was conducted in two stages: extraction of pepsin from the stomach of yellowfin tuna and production of enzymatic collagen hydrolysate using pepsin. The activities tested were 6,000, 9,000, and 12,000 U, with temperatures set at 40, 50, and 60°C. The extracted pepsin exhibited an activity of 12,332 U/mg pepsin. The ABTS antioxidant activity test revealed that the best IC50 value was achieved during hydrolysis at 50 °C, with values of 109 ppm for the 6,000 U treatment, 59 ppm for the 9,000 U treatment, and 230 ppm for the 12,000 U treatment. The most favorable IC50 value for DPPH antioxidant activity was observed during hydrolysis at 40°C, with respective values of 232, 194, and 531 ppm. Collagen hydrolysates at a concentration of 1.7 mg/mL of protein in each treatment showed inhibition values in the range of 40–66%.